Prevalence of confirmed immediate type drug hypersensitivity reactions among school children. Issue 2 (3rd February 2013) - Erkoçoğlu, Mustafa; Kaya, Aysenur; Civelek, Ersoy; Özcan, Celal; Çakır, Banu; Akan, Aysegül; Toyran, Müge; Ginis, Tayfur; Kocabas, Can Naci
Abstract Background Despite drug‐related hypersensitivity reactions are an important health problem, epidemiologic data on drug allergy and hypersensitivity are limited, and studies including diagnostic work‐up are scarce. The aim of this study was to determine the actual frequency of immediate type drug hypersensitivity using diagnostic tests in school children with parent‐reported drug allergies. Methods This study involved three phases. The first phase is a survey of children with a mean age of 12.9 yrs attending grades 6–8 of primary schools with a questionnaire asking drug‐related symptoms within 2 h of ingestion. The total population of sixth to eight grade school children was 210, 000, and a sample size of 9096 was deemed to be representative of Ankara [(p) = 1.0%, α < 0.05, β = 0.8, (d) = 0.2.] During the second phase, a detailed clinical history was obtained by phone from the parents of children who had positive parent‐reported drug allergy. The final stage of the study consisted of a detailed diagnostic work‐up of children with a clinical history consistent with immediate type drug hypersensitivity reaction. Results Overall, 11, 233 questionnaires were distributed, 10, 096 of which were retrieved after completion by parents. The rate of parent‐reported immediate type drug hypersensitivity was 7.87% (792 children). However, phone survey revealed a clinical history suggestive of drug allergy in only 117 children (1.16%). After further diagnostic work‐up, the true frequency of immediate type drug hypersensitivity was 0.11%. Conclusion Our results suggest that a positive clinical history is not enough to make a diagnosis of drug allergy, which highlights the significance of undertaking further diagnostic evaluation.